The effectiveness of advocacy sosiograph-based flipped classroom on students’ mathematical literacy in terms of self-regulated learning - Zainnur Wijayanto; Betty Kusumaningrum; Septin Atikarini; Indira Early; Esti Harini (UNION : Jurnal Ilmiah Pendidikan Matematika, 2026)
Mathematical literacy is an essential competency in 21st-century education; however, many students still experience difficulties in solving contextual mathematical problems due to passive and teacher-centered learning practices. This study aimed to investigate the effectiveness of the Advocacy Sociograph-Based Flipped Classroom model on students’ mathematical literacy in terms of Self-Regulated Learning (SRL). The study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The participants were eighth-grade students of SMP Muhammadiyah 1 Seyegan, consisting of 32 students in the experimental class and 28 students in the control class selected through cluster random sampling. Data were collected using mathematical literacy tests and SRL questionnaires and analyzed using a two-way ANOVA. The findings revealed that students taught using the Advocacy Sociograph-Based Flipped Classroom model achieved higher mathematical literacy scores than those taught using the conventional Flipped Classroom model. In addition, Self-Regulated Learning significantly influenced students’ mathematical literacy, and there was a significant interaction between the learning model and SRL. These findings indicate that integrating flipped learning, advocacy-based discussion, and sociograph-oriented group interaction can create a more effective and collaborative mathematics learning environment. Therefore, the proposed learning model may serve as an alternative instructional strategy for improving students’ mathematical literacy and independent learning skills.